An exploration of paired reading with a peer and its impact on the reading ability and school connectedness of looked-after hildren - Fry, Stephanie (2014)
This study explored the impact of paired reading, when delivered by a peer, on the reading ability and school connectedness of looked-after children (LAC). Relevant theory and research in three main areas is discussed: the under-achievement of LAC, reading development and difficulties and school connectedness. It is well understood that LAC are at risk of underachievement in reading (Department for Education, 2013), however they are an under-represented group in intervention research. Additionally, despite research illustrating the potential impact of school connectedness on a range of social, emotional and academic factors (Shochet et al, 2006 & Catalano et al, 2004) few studies have explored this with the LAC population. The present study attempted to address this by implementing a reading intervention using a peer approach with LAC. A single case experimental design was used with five participants. Weekly data was collected on reading accuracy, reading fluency and self-reported school connectedness. Pre and post data was also collected from teachers using two scales from the Strengths and Difficulties Questionnaire (SDQ): peer problems and pro-social behaviour. The results indicated a positive effect of paired reading on percentage reading accuracy, as shown in four of the five cases. Reading fluency did not significantly improve during the intervention for any of the participants. Similarly, school connectedness did not improve in three of the participants, although increased ratings were seen when paired reading was replaced with a non-reading intervention in three of the five participants. A significant difference in SDQ data was not observed. The study provides further evidence for the impact of paired reading on reading accuracy and suggests the potential for peer interventions to improve school connectedness. The discussion considered the generalizability of the findings and the nature of the measures used as potential limitations of this research. The study indicates the need for further research into school connectedness with LAC and highlights the potential role for EPs in recommending and supporting both academic and social interventions with this population.